Using a 3D-Printed Prosthetic to Improve Participation in a Young Gymnast. Issue 1 (January 2021) - Anderson, Brittany; Schanandore, James V.
Abstract : Background and Purpose: The purpose of this case report was to investigate the application of a 3-dimensional (3D)-printed prosthetic hand to improve a child's participation, confidence, and satisfaction in gymnastic classes, specifically, horizontal bar-related skills. Summary of Key Points: A 9-year-old child was unable to participate in horizontal bar-related gymnastic skills due to a congenital hand deficiency. A prosthetic hand was designed, 3D printed, modified repeatedly, and incorporated into a program, which resulted in improvements in the child's ability to participate in gymnastics. Conclusions: Using a 3D-printed upper limb prosthetic hand improved the child's participation, confidence, and satisfaction in her gymnastic classes permitting use of horizontal bar. To progress to higher-intensity activities, further safety measures and testing of the prosthetic hand are needed. What This Case Adds to Evidence-Based Practice: A 3D-printed prosthetic hand was manufactured and customized allowing closely monitored, gradually increased, participation in horizontal bar gymnastics. Abstract : The purpose of this case report was to investigate the application of a 3D-printed prosthetic hand to improve a child's participation, confidence, and satisfaction in gymnastic classes.